2019
DOI: 10.1002/asia.201900306
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalyst‐free Synthesis of Indazolones under CO2 Atmosphere

Abstract: A convenient photocatalyst‐free method for the synthesis of redox‐active 1,2‐dihydro‐3H‐indazol‐3‐one derivatives from (2‐nitroaryl)methanol and amines was developed. The reaction proceeded efficiently at room temperature by irradiation of UV light under CO2 atmosphere (1.0 atm, flow) without any photocatalysts or additives. This mild, operationally simple method shows wide functional tolerance. The carbamate formed in situ from CO2 and amine is proposed to be the key of this reaction. Some of these compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Recently, various photochemical methods for the synthesis of indazolin-3-ones were published (Scheme 2). [27][28][29][30] Despite the mild reaction conditions, one of the two reactants has to be used in excess, leading to increased reagent waste. Moreover, only very few 2-aryl substituted indazolin-3-one derivatives have been reported, and in most cases only poor yields were obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, various photochemical methods for the synthesis of indazolin-3-ones were published (Scheme 2). [27][28][29][30] Despite the mild reaction conditions, one of the two reactants has to be used in excess, leading to increased reagent waste. Moreover, only very few 2-aryl substituted indazolin-3-one derivatives have been reported, and in most cases only poor yields were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only very few 2-aryl substituted indazolin-3-one derivatives have been reported, and in most cases only poor yields were obtained. [27][28][29][30] Another powerful and broadly applicable synthetic tool for the synthesis of N-heterocyclic structures is electro-organic chemistry. 31 The direct use of inexpensive electric current as the redox reactant enables the replacement of polluting and dangerous oxidizing and reducing agents, diminishing reagent waste, 32 increasing work safety, and lowering costs.…”
Section: Introductionmentioning
confidence: 99%
“…developed another efficient route using inexpensive Brønsted acid catalysts to promote a redox amination process, which could efficiently realize the multistep coupling of anilines and indolines to synthesize N -aryl-1-amino indoles (Scheme b) . Inspiring by these ideas and our previous finding about o -nitrobenzyl alcohols, herein, we disclosed a protocol which realize the construction of N -aryl-1-amino indoles in one-pot by a redox coupling process (Scheme c). The inexpensive o -nitrobenzyl alcohols could produce the oxidized intermediates via a photoinduced method, which can construct N–N bonds with indolines.…”
mentioning
confidence: 99%
“…However, our group recently demonstrated that the key nitroso imine intermediate can be generated in situ under photochemical conditions in aqueous PBS solution and subsequently intercepted by primary amines (Scheme ). Kambe and Chen more recently reported similar photochemical methods leading to indazolones, but it should be noted that accessing N -aryl products using their methods remains problematic. Development of these photochemical methods gave us the experimental flexibility required to study the highly reactive nitroso intermediates under Brønsted acid catalysis (Scheme B).…”
mentioning
confidence: 99%
“…Instead, N -aryl indazolone 12a (64%; 12b in 71% from p -anisidine) was formed, either by addition of H 2 O instead of tert -butanol to 57 (see Figure ) or by acid-mediated hydrolysis of indazole 12 (see SI for additional discussion). Obtaining 12a and 12b represents a major improvement over other direct methods for N -aryl indazolone synthesis (see Scheme A). , While p -aminopyridine did not give 13 , naphthalen-2-amine successfully gave 14 in 75% yield. Comparing 15 vs 16 highlights the role of reactive intermediate steric demands, while comparing 18 vs 19a/19b / 20 highlights substrate electonic effects on reaction outcome.…”
mentioning
confidence: 99%